Attendance System Implementation Existing Android Platform Using React Native Framework - Bakti Nugraha, Arif; Rizcky Hikmawan, Muhammad (CoreID Journal, 2023)
In a school that has hundreds of students, the attendance system or attendance recording is a problem in terms of practicality and data capture. Especially during a pandemic like this, learning is carried out online or in a network, commonly called distance learning (PJJ). Currently, various applications of technological advances have been created and begun to replace conventional systems. One of them is an Android-based attendance application system. The purpose of this study is to analyze and design an application that can help manage attendance data more easily and accurately. System modeling uses Unified Modelling Language (UML) to describe visually, then implemented with PHP and JavaScript programming languages, React Native Framework, and MySQL database as a database. With the mobile-based attendance system, it can make it easier for teachers to conduct attendance effectively and efficiently.